Depression, thwarted belongingness, perceived burdensomeness, and suicidal behavior among undergraduate students: a quantitative study in Malaysia - Hoh, Ee Ling; Ismail, Asmah (Human Resource Management Academic Research Society, 2020)
Among Malaysian undergraduate students, little is known about the risk factors associated with suicidal behavior. The aim of this study was to examine the relationships among undergraduate students between depression, burdensomeness, thwarted ownership, and suicidal behavior. The study surveyed 120 undergraduate students in Peninsular Malaysia from a public university. Pearson's Correlation and multiple linear regression were used to evaluate the data. The result shows that around 20% of the participants tend to engage in suicidal behavior. Generally, there is a significant correlation between depression [r(119) = .623, p<.50], thwarted belongingness [r(119) = .397, p<.50], perceived burdensomeness [r(119) = .363, p<.50], and interpersonal needs [r(119) = .443, p<.50], with suicidal behavior among the participants. Among the three variables, only depression significantly predicts suicidal behavior (R²= .40, F (3, 115) = 25.855, p< .05) with the explanation of 38.7%. These findings convey an important message to the student affairs section and counselling unit to conduct periodical mental health screening. Special attention should be given to curtail the role of depression as the catalyst in suicide actions.